1991
DOI: 10.1126/science.1708917
|View full text |Cite
|
Sign up to set email alerts
|

Presence of an SH2 Domain in the Actin-Binding Protein Tensin

Abstract: The molecular cloning of the complementary DNA coding for a 90-kilodalton fragment of tensin, an actin-binding component of focal contacts and other submembraneous cytoskeletal structures, is reported. The derived amino acid sequence revealed the presence of a Src homology 2 (SH2) domain. This domain is shared by a number of signal transduction proteins including nonreceptor tyrosine kinases such as Abl, Fps, Src, and Src family members, the transforming protein Crk, phospholipase C-gamma 1, PI-3 (phosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(152 citation statements)
references
References 31 publications
4
148
0
Order By: Relevance
“…Tensin includes both phosphorylated tyrosine residues and a Src homology 2 (SH2) domain, which is shared by a number of signal transduction proteins [34]. It is suggested that tensin may link signal transduction pathways with the cytoskeleton by possessing both actin-binding and phosphotyrosine-binding properties and being itself a target for tyrosine kinases [35]. Since GAK also has tensin-like properties such as an actin-binding domain and a target site for tyrosine kinases, it is conceivable that GAK plays a similar role in the cytoskeletal signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tensin includes both phosphorylated tyrosine residues and a Src homology 2 (SH2) domain, which is shared by a number of signal transduction proteins [34]. It is suggested that tensin may link signal transduction pathways with the cytoskeleton by possessing both actin-binding and phosphotyrosine-binding properties and being itself a target for tyrosine kinases [35]. Since GAK also has tensin-like properties such as an actin-binding domain and a target site for tyrosine kinases, it is conceivable that GAK plays a similar role in the cytoskeletal signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the middle part of the molecule (Fig. 1C), GAK resembles both tensin, an actin-binding component of adhesion plaques (also called focal contacts) and other submembranous cytoskeletal structures [16], and auxilin, a coat component of brain clathrin-coated vesicles [17,18]. The domain homologous to tensin and auxilin (we call it the TAG domain hereafter) occupies more than half of the whole molecule and contains, in addition, a leucine zipper region [19] in the C-terminal portion of this domain.…”
Section: Molecular Cloning Of Gakmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosine phosphorylation of tensin (Davis et al, 1991), talin (DeClue and Marin, 1987), p120 (Kanner et al, 1990;Reynolds et al, 1992), p80/85 (cortactin) (Wu et al, 1991) and paxillin (Turner et al, 1990) was greatly reduced or became almost undetectable when the cell to substratum adhesion was lost (Figure 2). Tyrosine phosphorylation of these proteins was then restored to similar to the original levels when the cells in suspension were spread on ®bronectin-coated culture dishes in the absence of serum (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…These proteins may have signal protein binding domains such as SH2 and SH3 domains (Feller et al, 1994) or binding motifs for these domains, or they may bind adaptor proteins which link them to signaling proteins (Feller et al, 1994;Birge et al, 1996). For example, the actinbinding protein tensin (Lo et al, 1994a) contains an SH2 domain (Davis et al, 1991), implicating this membrane skeletal protein in linking signal transduction to the cytoskeleton (Lo et al, 1994b). Although their cellular functions are yet poorly understood, SH3 domains have also been strongly implicated in cellular localization of signaling elements to activated receptors and to the membrane-cytoskeleton interface .…”
Section: Introductionmentioning
confidence: 99%